(untitled) (Nuntius Antiquus, 2009)
In this article, we analyse the structure of two poems by Sappho (Fr. 1 and Fr. 31), for which we present a poetic translation. It is followed by a commentary on stylistic aspects of the poems and the way they were recreated (or not) in the translation.